2022
DOI: 10.1007/s11033-022-07624-6
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of fibrinogen-like protein-1 expression with the progression and prognosis of hepatocellular carcinoma

Abstract: Background Fibrinogen-like-protein 1 (FGL1), a member of the fibrinogen-related protein (FREP) family, is a major ligand of the immune inhibitory receptor lymphocyte-activation gene 3 (LAG-3). While FGL1 is strongly implicated in the development and prognosis of a variety of diseases, its role in hepatocellular carcinoma (HCC) is still disputed. Therefore, the role of FGL1 expression in the progression and prognosis of HCC was investigated. Methods and results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…The results of Lin et al indicate that FGL1 expression is a negative prognosticator in HCC, as demonstrated by the association between FGL1 inhibition, antitumor immunity, and survival ( 4 ). Notably, these results contrast with prior findings in which downregulation of FGL1 in HCC increases the rates of tumor formation ( 15 17 ), and is a positive prognosticator ( 15 ). The discrepancy between the present study and others may be a function of analyzing the different ways in which FGL1 influences the development and progression of HCC.…”
Section: The Role Of Fgl1 In Hepatocellular Carcinomacontrasting
confidence: 99%
“…The results of Lin et al indicate that FGL1 expression is a negative prognosticator in HCC, as demonstrated by the association between FGL1 inhibition, antitumor immunity, and survival ( 4 ). Notably, these results contrast with prior findings in which downregulation of FGL1 in HCC increases the rates of tumor formation ( 15 17 ), and is a positive prognosticator ( 15 ). The discrepancy between the present study and others may be a function of analyzing the different ways in which FGL1 influences the development and progression of HCC.…”
Section: The Role Of Fgl1 In Hepatocellular Carcinomacontrasting
confidence: 99%
“…Hence, FGL1 expression is linked to HCC progression and prognosis, supporting its use as a biomarker. 44 Another study investigated the association of the FGL1-LAG-3 pathway and programmed cell death ligand 1 (PD-L1) with prognosis in HCC. LAG-3, FGL1, PD-L1, and CD8 + T cells were measured in 143 HCC patients.…”
Section: Hepatectomy In Patients With Hcc and The Possible Role Of Fgl1mentioning
confidence: 99%
“…Moreover, FGL-1 expression within the tumor appeared to be correlated with the progression and prognosis of HCC, suggesting that FGL-1 could be used not only as a molecular target but also as a potential prognostic biomarker. 67 More research is needed in order to understand if LAG-3 through FGL-1 blockade could have a role as a new therapeutic strategy to overcome resistance to immunotherapy. In addition to its therapeutic role, it will be important to analyze the prognostic potential of FGL as a prognostic marker.…”
Section: Tumor-intrinsic Mechanisms Of Resistancementioning
confidence: 99%